Rytmy czasu, meandry pamięci. O poezji Bogusławy Latawiec - Rygielska, Małgorzata (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
This paper deals with the problems of time and temporality in the poetry of Bogusława Latawiec ranging from one of her first volumes of poetry (Przestrzenie [Spaces ], 1975) to the recently released Zmowy [Collusions] (2015). The passage of time, various ways of perceiving and sensing it are the overarching themes of her oeuvre (both prose and poetry). Her poetry, characterized by a remarkable linguistic discipline, a skillful use of formal devices and a close connection between the images and the sonic layer of her poems, highlights the importance of linking the experience of time and its passage with the issues of subjectivity and identity. Personal time converges here with historical, physical and mechanical time. It gains a material dimension: it becomes measurable and even tangible. This is noticeable in the poet’s latest minor volumes: Gdyby czas był ziemią [If time was the Earth ] (2011) and in Zmowy [Collusions ] (2015).